Manajemen Kelas Khusus Olahraga Untuk Branding Madrasah Tsanawiyah Negeri 6 Sragen - Suryono Suryono; Baidi Baidi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine the sports class management strategy at MTsN 6 Sragen and its impact on the image of the madrasah. The establishment of dedicated sports classes in educational institutions in Indonesia, including religious-based schools, is a relevant innovation for optimizing student potential, both in academic and non-academic areas. Using a qualitative approach and case study method, this study collected data through in-depth interviews with various stakeholders, such as the madrasah principal, program coordinator, sports teachers, and students. The results identified four main themes: (1) sports class management as a form of educational innovation, (2) the role of sports in character building and the image of the madrasah, and (3) challenges faced in implementing sports classes, and (4) contributions within the community to strengthen madrasa branding. Despite various obstacles, such as limited facilities and budget, sports classes have great potential to contribute to improving the image of madrasas and developing student character. This study also highlights the importance of support from internal stakeholders and the external community in ensuring the successful management of sports classes and enhancing the reputation of madrasas. The findings of this study provide an overview of the importance of integrating sports into educational strategies and its impact on comprehensive student character development, which in turn can strengthen the positive image of the institution.